A human lung mast cell chymotrypsin-like enzyme. Identification and partial characterization. - Wintroub, B U (1986)
We have used a high performance liquid chromatography assay, which detects chymotryptic cleavage of the phe8-his9 bond of angiotensin I to yield angiotensin II, in order to examine human lung mast cells for the presence of chymotryptic activity. Mast cells, purified from human lung by enzymatic dispersion, countercurrent elutriation, and Percoll gradient centrifugation, were lysed or challenged with goat anti-human IgE. In multiple experiments angiotensin II-converting activity was detected in lysates of 10-99% pure mast cell preparations. Regression analysis of net percent release values of histamine and the angiotensin I-converting activity from dose-response experiments demonstrated a correlation between the two parameters, indicating that the chymotrypsin-like enzyme is a constituent of the mast cell secretory granule. The chymotryptic activity was completely inhibited by 10(-3) M phenylmethylsulfonylfluoride but not by 10(-3) M Captopril, and the pH optimum of activity was 7.5-9.5. Gel filtration of released material separated the activity from tryptase and demonstrated an approximate molecular weight of 30-35,000. The mast cell enzyme, like a human skin chymotrypsin-like proteinase, can be distinguished from leukocyte cathepsin G by lack of susceptibility to inhibition by bovine pancreatic trypsin inhibitor. Thus, an enzyme with limited chymotryptic specificity is present in human lung mast cells. The Michaelis constant of the enzyme for angiotensin I of 6.0 X 10(-5) M is similar to that of endothelial cell angiotensin-converting enzyme and is consistent with a reaction of physiologic importance.